Pengaruh Capital Adequacy Ratio (CAR), Return On Assets (ROA), dan Non Performing Financial (NPF) Terhadap Penyaluran Pembiayaan pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode Tahun 2012–2019 - Irma Citarayani; Melani Quintania; Dita Paramita Handayani (Akuisisi: Jurnal Akuntansi, 2021)
The purpose of this research is to see the effect of pentagon fraud that proxied by financial targets, nature of the industry, quality of external auditors, change of auditors, number of CEOs who frequently detect fraud in financial statements. Financial statement fraud in this study was measured using the proxies of Return on Assets, Receivables, selection of audit services at public accounting firms, changes in public accounting firms, changes in directors, and the number of CEO photos. The population in research study are use manufacturing companies who listed on the Indonesia Stock Exchange (BEI) in 2017-2019. This research uses a purposive sampling technique so, there are 48 financial reports from 25 manufacturing companies. The analytical method used in this research is multiple linear regression analysis with SPSS version 20. The results of this research indicate that financial targets, nature of industry, quality of external auditors and the number of CEOs who often don’t have a significant effect in the handling of fraudulent financial statements. Meanwhile, changes in auditors and changes in direction have a significant effect from pentagon fraud side on fraudulent financial statements. Tujuan penelitian ini adalah untuk melihat pengaruh fraud pentagon yang di proksikan dengan financial target, nature of industry, quality of external auditor, change of auditor, frequent number of CEO terhadap pendeteksian kecurangan (fraud) laporan keuangan. Kecurangan dalam Laporan Keuangan di penelitian ini diukur menggunakan proksi Return on Assets, Receivable, pemilihan jasa audit pada KAP, pergantian KAP, perubahan direksi, dan banyaknya foto CEO. Perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2017-2019 digunakan sebagai populasi dalam penelitian ini. Penelitian ini menggunakan teknik purposive sampling sehingga terdapat 48 laporan keuangan dari 25 perusahaan manufaktur. Analisis regresi linear berganda merupakan metode analisis yang digunakan dengan SPSS versi 20. Financial target, nature of industry, quality of external auditor dan frequent number of CEO tidak bepengaruh signfikan dalam mendeteksi adanya kecurangan dalam Laporan Keuangan dalam penelitian ini. Sedangkan, change of auditor dan change of direction berpengaruh signifikan dalam medeteksi kecurangan dalam laporan keuangan.